Dairy facility design - J.P. Muprhy (Kansas Agricultural Experiment Station Research Reports, 1989)
When planning new construction or major modification of a dairy system, consider: "¢ calf, heifer, dry cow, and milking cow housing; "¢ feed types, handling equipment, and storage; "¢ manure handling method; "¢ milking system and equipment; "¢ labor requirements; "¢ building environment; "¢ sanitary and pollution control regulations; "¢ future expansion. Many dairy farmers produce their own feeds and raise their own herd replacements. The needs of each groups require different housing, feeding, storage, and handling systems.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Facility design; Housing; Feed